CHARACTERISTICS AND CRITERIA OF BUDGET SYSTEM IMPROVEMENT BASED ON GREEN BUDGETING - Rakhmanov Mukhammadeldar Abduvakhidovich (Scholar Express Journals, 2023)
This article describes in detail the specific features of improving the budget system based on green budgeting and green financing. On the basis of green budgeting, elements and tools of the state budget affecting sustainable ecological balance and environmental policy are analyzed. Also, criteria for improving the budget system based on green budgeting have been developed
Keywords: green budget; budget system green finance; green bond; green fund